A study of drug utilization pattern and pharmacoeconomic of antidiabetic drugs in patients attending a teaching hospital - M., Shanthi (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug utilization research establishes the current trend in the use of antidiabetic drugs including the new drug and to identify irrational prescription. Methods: A cross-sectional study was conducted for a period of one year (between August 2013 to August 2014) at outpatient department of Medicine, Sree Mookambika Institute of Medical Sciences, Kulasekharam, Kanyakumari District, Tamil Nadu. Results: A total of 169 prescriptions were evaluated during the study period. Diabetes mellitus was predominant among the female population in this region. Demographic details of the patient included in the study were mean weight 67.56kg, mean height 155cm and average body mass index 27.82kg/m2. All the patients were diagnosed and were known case of type 2 diabetes mellitus. Systemic hypertension was the frequently encountered co-morbid conditions associated with this endocrine disorder. Metformin was the drug chosen for managing diabetes as monotherapy and 73% of the patients were on combination of antidiabetic drugs. Glimepiride with metformin was the combination therapy frequently prescribed during the study period. Pharmacoeconomic analysis identified that drugs prescribed by brand name were costlier compared to generic equivalent. Conclusions: Utilization of antidiabetic drug therapy in this region has shown a changing trend compared to the previous studies. There is a gradual increase in the prescription of metformin and dramatic increase in the use of newer drugs like pioglitazone, voglibose and sitagliptin. Pharmaeconomic analysis revealed that glibenclamide was least expensive while sitagliptin was most expensive in this study.